M-Learning applied to the improvement of the learning of university engineering students - Petrlik Azabache, Iván (2020)
This paper is intended to determine the extent to which the M-learning model with methodological strategies improves the learning of student’s undergraduates of the Systems Engineering career. The method used was developed through a study of quasi-experimental type and conformed by an experimental group composed of 25 students of section B and a control group by 25 students of section A of the subject of Software Design Patterns. of the Autonomous University of Peru. To obtain the results of the inferential analysis, the Student T test and the Mann Whitney U test were used. Likewise, a prestest and a posttest were applied to evidence the learning improved, previously tests of validity and reliability were performed in each case, the corresponding calculations were subsequently made for the test of the hypotheses. After applying the M-learning model with methodological strategies, significant differences were observed (p = 0.000 <0.05) in the general, declarative, procedural and attitudinal learning, in the results of the pretest and posttest evaluation, being higher the average of the posttest, with a 95% level of confidence. With the results obtained, we can conclude that the M-learning model with methodological strategies significantly improves the learning of university students of the Systems Engineering career of the Autonomous University of Perú in the subject of Software Design Patterns.